2015
DOI: 10.1902/jop.2014.140450
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Associations Between Interleukin‐8 Polymorphisms and Periodontitis Susceptibility

Abstract: This meta-analysis indicated that both IL-8 -251A/T and -845T/C polymorphisms may be involved in the development of periodontitis in a Brazilian mixed population, whereas the -251A/T allele T appeared to be a risk factor for periodontitis in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Recent studies have indicated that polymorphisms in IL-8 could influence the development of various diseases, including acne vulgaris, glioma, gastric diseases, periodontitis, osteoarthritis, ovarian cancer, and oral cancer, as well as acute pancreatitis He et al, 2014;Chen et al, 2015;Hussain et al, 2015;Koensgen et al, 2015;Liu et al, 2015;Ramis et al, 2015). Wang et al (2013) observed, in a meta-analysis of 1324 patients with oral cancer and 1879 healthy controls, that the AA and AT genotypes of IL-8 rs4073 was correlated with an increased risk of oral cancer in a Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that polymorphisms in IL-8 could influence the development of various diseases, including acne vulgaris, glioma, gastric diseases, periodontitis, osteoarthritis, ovarian cancer, and oral cancer, as well as acute pancreatitis He et al, 2014;Chen et al, 2015;Hussain et al, 2015;Koensgen et al, 2015;Liu et al, 2015;Ramis et al, 2015). Wang et al (2013) observed, in a meta-analysis of 1324 patients with oral cancer and 1879 healthy controls, that the AA and AT genotypes of IL-8 rs4073 was correlated with an increased risk of oral cancer in a Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, He et al (2014) reported, in a case-control study with 150 osteoarthritis patients and 150 controls, that the TT genotype and the T allele of IL-8 rs4073 and rs2227306 polymorphisms conferred an elevated risk of osteoarthritis. Chen et al (2015) reported that the IL-8 rs407 polymorphism may be involved in periodontitis susceptibility in Brazilian and Asian populations, while Koensgen et al (2015) reported a correlation between the TT genotype of IL-8 rs2227306 and a higher risk of ovarian cancer. Hussain et al (2015) hypothesized that elevated IL-8 levels and the IL-8 rs4073 genetic variant may be correlated with acne vulgaris in a Pakistani population and Liu et al (2015) reported that the AA genotype of the IL-8 rs4073 polymorphism conferred a significantly higher risk of glioma, compared to the TT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis evidenced that the IL-8 −251A/T polymorphism is related with a decreased risk of periodontitis in a Brazilian mixed population and an increased risk of periodontitis in an Asian population. The IL-8 gene has q13-q12 localization on chromosome 4, where the −251 A/T variant is related to an increase in the transcriptional activity of this cytokine [23]. The evidence that IL-8 −251A/T A allele is associated with higher expression of IL-8 can be observed in patients with chronic periodontitis in which higher IL-8 levels in the gingival crevicular fluid than healthy individuals were found.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence that IL-8 −251A/T A allele is associated with higher expression of IL-8 can be observed in patients with chronic periodontitis in which higher IL-8 levels in the gingival crevicular fluid than healthy individuals were found. In addition, the expression of IL-8 in gingival epithelial cells can be induced by Porphyromonas gingivalis and Tannerella forsythia [23], bacteria commonly associated with periodontitis. It is important to note that although a very low genetic diversity was observed for the −845T/C polymorphism, the authors verified that Brazilian individuals with variant genotypes presented a higher risk of chronic periodontitis [23].…”
Section: Resultsmentioning
confidence: 99%
“…The meta‐analysis in Song et alanalyzed the combined effect of 2 of the Nibali TNF studies and found no significance. The IL8 meta‐analysis by Chen et al included 3 of the studies described here but the only significant observation was that T allele rs4073 was associated with increased risk of periodontitis in a Brazilian mixed population (includes some African background), which also showed marginal association of the other IL8 SNP (rs2227532) . The studies reported in this review nearly all had small subject numbers: most had fewer than 70 affected individuals (some much less), particularly of African descent.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%